EVL regulates VEGF receptor‐2 internalization and signaling in developmental angiogenesis. (29th January 2021) - Zink, Joana; Frye, Maike; Frömel, Timo; Carlantoni, Claudia; John, David; Schreier, Danny; Weigert, Andreas; Laban, Hebatullah; Salinas, Gabriela; Stingl, Heike; Günther, Lea; Popp, Rüdiger; et al.
Abstract: Endothelial tip cells are essential for VEGF‐induced angiogenesis, but underlying mechanisms are elusive. The Ena/VASP protein family, consisting of EVL, VASP, and Mena, plays a pivotal role in axon guidance. Given that axonal growth cones and endothelial tip cells share many common features, from the morphological to the molecular level, we investigated the role of Ena/VASP proteins in angiogenesis. EVL and VASP, but not Mena, are expressed in endothelial cells of the postnatal mouse retina. Global deletion of EVL (but not VASP) compromises the radial sprouting of the vascular plexus in mice. Similarly, endothelial‐specific EVL deletion compromises the radial sprouting of the vascular plexus and reduces the endothelial tip cell density and filopodia formation. Gene sets involved in blood vessel development and angiogenesis are down‐regulated in EVL‐deficient P5‐retinal endothelial cells. Consistently, EVL deletion impairs VEGF‐induced endothelial cell proliferation and sprouting, and reduces the internalization and phosphorylation of VEGF receptor 2 and its downstream signaling via the MAPK/ERK pathway. Together, we show that endothelial EVL regulates sprouting angiogenesis via VEGF receptor‐2 internalization and signaling. SYNOPSIS: This study reveals that the Ena/VASP protein family member EVL is a regulator of endothelial cell proliferation and sprouting in the postnatal retina. Genetic deletion of EVL (but not its homolog VASP) impairs the radial sprouting of the retinal vascular plexus and reduces endothelial cell proliferation, tip cell density and filopodia formation in the retina. EVL depletion impairs VEGF‐induced endothelial cell proliferation and sprouting in vitro and ex vivo . EVL depletion reduces the internalization and phosphorylation of VEGF receptor‐2 and its downstream signaling via the MAPK/ERK pathway. Abstract : This study reveals that the Ena/VASP protein family member EVL is a regulator of endothelial cell proliferation and sprouting in the postnatal retina.